The Bluedisk survey: molecular gas distribution and scaling relations in the context of galaxy evolution. Issue 2 (22nd August 2016) - Cormier, D.; Bigiel, F.; Wang, J.; Pety, J.; Usero, A.; Roychowdhury, S.; Carton, D.; van der Hulst, J. M.; Józsa, G. I. G.; González-García, M.; Saintonge, A.
Abstract: One of the key goals of the Bluedisk survey is to characterize the impact of gas accretion in disc galaxies in the context of galaxy evolution. It contains 50 disc galaxies in the stellar mass range 10 10 –10 11  M⊙, of which half are bluer and more H i -rich galaxies than their H i -normal (control) counterparts. In this paper, we investigate how ongoing disc growth affects the molecular gas distribution and the star formation efficiency in these galaxies. We present 12 CO observations from the IRAM 30-m telescope in 26 galaxies of the Bluedisk survey. We compare the amount and spatial distribution of the molecular gas to key quantities such as atomic gas, stellar mass and surface density, star formation rate (SFR) and metallicity. We analyse the SFR per unit gas (SFR/H i and SFR/H2 ) and relate all those parameters to general galaxy properties (H i -rich/control disc, morphology, etc.). We find that the H i -rich galaxies have similar H2 masses as the control galaxies. In their centres, H i -rich galaxies have lower H2 /H i ratios and marginally shorter molecular gas depletion times. However, the main differences between the two samples occur in the outer parts of the discs, with the H i -rich galaxies having slightly smaller CO discs (relative to the optical radius R 25 ) and steeper CO and metallicity gradients than the control galaxies. The ongoing accretion of H i at large radii has thus not led to an appreciable growth of the CO discs in our sample. Based on depletion times, we estimate that this gas will contribute to star formation on time-scales of at least 5 Gyr.